Identification of Clock Genes Related to Hypertension in Kidney From Spontaneously Hypertensive Rats. (14th October 2020) - Murata, Yusuke; Ueno, Takahiro; Tanaka, Sho; Kobayashi, Hiroki; Okamura, Masahiro; Hemmi, Seiichiro; Fuke, Yoshinobu; Matsumoto, Yoshiaki; Abe, Masanori; Fukuda, Noboru
Abstract: Background: There is a diurnal variation in the blood pressure fluctuation of hypertension, and blood pressure fluctuation abnormality is considered to be an independent risk factor for organ damage including cardiovascular complications. In the current study, we tried to identify molecules responsible for blood pressure circadian rhythm formation under the control of the kidney biological clock in hypertension. Methods: DNA microarray analysis was performed in kidneys from 5-week-old spontaneously hypertensive rats (SHRs)/Izm, stroke-prone SHR rats (SHRSP)/Izm, and Wistar Kyoto (WKY)/Izm rats. To detect variation, mouse tubular epithelial cells (TCMK-1) were stimulated with dexamethasone. We performed immunostaining and western blot analysis in the renal medulla of kidney from 5-week-old WKY rats and SHRs. Results: We extracted 1, 032 genes with E-box, a binding sequence for BMAL1 and CLOCK using a Gene Set Enrichment Analysis. In a microarray analysis, we identified 12 genes increased as more than 2-fold in the kidneys of SHRs and SHRSP in comparison to WKY rats. In a periodic regression analysis, phosphoribosyl pyrophosphate amidotransferase (Ppat) and fragile X mental retardation, autosomal homolog 1 (Fxr1) showed circadian rhythm. Immunocytochemistry revealed PPAT-positivity in nuclei and cytoplasm in the tubules, and FXR1-positivity in the cytoplasm of TCMK-1. In 5-week-old WKY rat and SHR kidneys, PPAT was localized in the nucleus and cytoplasm of the proximal and distal tubules, and FXR1 was localized to the cytoplasm of the proximal and distal tubules. Conclusions: PPAT and FXR1 are pivotal molecules in the control of blood pressure circadian rhythm by the kidney in hypertension.